The Impact of Artificial Intelligence on Auditing Practices and Financial Reporting Accuracy - Muftah, Mohammed Abu Reemah Ahmed (Integrated Journal for Research in Arts and Humanities, 2022)
The transformational effects of artificial intelligence (AI) on auditing procedures and financial reporting accuracy are examined in this study article. This research looks at how artificial intelligence (AI) tools, such data analytics and machine learning, are changing auditing by making it more efficient, lowering the risk of human mistake, and boosting the ability to spot fraud. The study outlines the advantages and difficulties of using AI in auditing via a thorough examination of the literature and an analysis of current trends. Based on important discoveries, AI-powered audits may greatly improve the timeliness and dependability of financial reporting, enabling stakeholders to make better decisions. However, there are drawbacks to integrating AI as well, such as the need for large training and technological expenditures as well as possible ethical and security issues. In order to fully use AI in auditing while managing the related dangers, the study ends with suggestions for practitioners and policymakers. By offering insightful information to academics, business professionals, and regulators, this study adds to the continuing conversation on auditing's future in the digital era.